IL-38 promotes the development of prostate cancer - Wu, Huiyan; Yang, Jing; Yuan, Liuhong; Tan, Zhenyu; Zhang, Xiuqin; Hambly, Brett D.; Bao, Shisan; Tao, Kun (Frontiers in Immunology, 2024)
Introduction: Prostate Cancer (PCa) remains a significant concern in male cancer-related mortality. Tumour development is intricately regulated by the complex interactions between tumour cells and their microenvironment, making it essential to determine which is/are key factor(s) that influence the progression of PCa within the tumour microenvironment. Results: The current study utilized histopathology and immunohistochemistry to determine the expression of IL 38 in PCa and analysed the correlation between the expression level of IL-38 within PCa and clinical pathological characteristics. There was a significant increase in IL 38 expression in PCa tissues compared to adjacent non-PCa tissues (P < 0.0001). In addition, IL-38 expression was significantly higher in tumour cells with a high proliferation index compared to those with a low value-added index. ROC curve analysis demonstrated that IL-38 has high specificity and sensitivity for the diagnosis of PCa (AUC=0.76). Moreover, we Probed the cellular source of IL-38 in prostate cancer tissue by immunofluorescence double staining. Additionally, within PCa, the expression of IL-38 was inversely correlated with the expression levels of CD8 and PD-1. Survival analysis revealed a significantly lower overall survival rate for PCa patients with high IL-38 expression (P=0.0069), and when IL-38 was co-expressed with CD8, the survival rate of the IL 38high/CD8low group was decreased significantly. Multivariate analysis indicated that the expression level of IL-38 and TNM staging were independent predictors of survival in PCa patients. Conclusion: These findings suggest that IL-38 plays a crucial role in the development of PCa, and the exploration of the correlation between IL-38 and various immune factors in the tumour microenvironment further reveals its mechanism of action, making it a potential target for immunotherapy in PCa.